Semi-arid regions of the boreal zone as demonstrated in the Yukon Basin - Jätzold, Ralph (ERDKUNDE, 2000)
The comparison of precipitation and potential evapotranspiration (calculated by the Penman formula and verified by several measurements) shows a semi-arid to arid period in the interior of Alaska and the Canadian Yukon Territory mostly from April to August. This water deficit is normally not evident in the forest vegetation because of the trees' compensation by an extremely slow growth rate. If the most critical season from April to June, however, is very arid then forest thins out on free draining sites (where the snow-melt water runs off before it can infiltrate the still frozen soil). On south-facing slopes aspen parklands, prairies and sagebrush manifest the increasingly arid conditions. Melt water is irrelevant there because the snow-cover becomes discontinuous through the effects of wind and in late winter of the sun, which causes higher microclimatic temperatures and evaporation than anticipated. The remaining water is lost by runoff. Dall sheep and - up to Faro - the southern variety of stone sheep depend on these slopes for survival during winter. Agricultural projects attracted by the relatively high summer temperature failed partially due to water stress. The farmers need to irrigate. Semi-arid regions in the boreal zone are typical of its inner portion (where the anticyclonic air dominates in winter and cyclonic moist air is kept off in summer). These intrazonal regions are slightly shifted by azonal mountain ranges: in North America westward and in Siberia eastward.